Fluorescent glass, preparation method thereof and automobile headlamp
By preparing fluorescent glass composed of Y3Al5O12:Ce3+ and specific matrix glass, the existing fluorescent glass has solved the problems of low light efficiency and insufficient thermal conductivity, and the high thermal conductivity, luminous efficiency and transmittance are improved, and it is suitable for modern automotive headlight systems.
Patent Information
- Application Number
- CN202510064761.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-25
AI Technical Summary
The existing fluorescent glass has low light efficiency, insufficient thermal conductivity, and poor luminous intensity and transmittance, making it difficult to meet the needs of modern automotive headlight systems for energy efficiency, life and environmental adaptability.
Fluorescent glass is prepared by sintering Y3Al5O12:Ce3+ phosphor with a specific matrix glass powder at high temperature, which consists of 35 to 45 parts by weight of Y3Al5O12:Ce3+ and 55 to 65 parts by weight of matrix glass. The matrix glass is composed of SiO2, B2O3, Na2O, ZnO and CaO, and its content range is controlled.
The thermal conductivity, luminous efficiency, luminous intensity and light transmittance of fluorescent glass are improved, and the light transmittance in the 300-800nm band are met by modern automotive headlight systems for high efficiency, long life and environmental adaptability.
Smart Images

Figure CN119874183A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to fluorescent glass and a preparation method thereof and an automobile headlight. Background Art
[0002] The development of modern automobile headlight systems is committed to improving driving safety, energy efficiency and design flexibility, but its energy efficiency is low, life is short, and its adaptability to the environment is poor. Traditional automobile headlights usually use halogen lamps or xenon lamps. LED technology, as a high-efficiency and long-life light source, has gradually replaced the position of traditional lighting systems.
[0003] CN101643315A discloses a low melting point fluorescent glass for white light LED, which is prepared from raw materials containing Na2O, ZnO, B2O3, SiO2, Al2O3, CaO, MgO, K2O and Ce-YAG components, wherein the mass percentage of each component is Na2O 1-20%, ZnO 0-20%, B2O3 20-40%, SiO2 10-30%, Al2O3 1-25%, CaO 0-10%, MgO 0-4%, K2O 0-1.5%, Ce-YAG 5-30%. The light efficiency of the fluorescent glass is low.
[0004] CN105121375A discloses a fluorescent dispersed glass, which is a fluorescent dispersed glass in which fluorescent particles are dispersed in the glass, and the glass comprises 1-40 mass % SiO2, 15-65 mass % B2O3, 1-50 mass % ZnO, 0-40 mass % RO, i.e., the total of at least one selected from the group consisting of MgO, CaO, SrO and BaO, 0-30 mass % R2O, i.e., the total of at least one selected from the group consisting of Li2O, Na2O and K2O, and 0-5 mass % ZrO2; wherein SiO2+B2O3+ZnO+RO+R2O+ZrO2 is 80 mass % or more. The light efficiency of the fluorescent glass is low. Summary of the invention
[0005] In view of this, one object of the present invention is to provide a fluorescent glass having a high luminous efficiency. Further, the fluorescent glass has a high thermal conductivity. Further, the fluorescent glass has a high luminous intensity and transmittance. Another object of the present invention is to provide a method for preparing the fluorescent glass. Still another object of the present invention is to provide a car headlight.
[0006] The present invention achieves the above technical objectives through the following technical solutions.
[0007] In one aspect, the present invention provides a fluorescent glass comprising 35 to 45 parts by weight of Y3Al5O 12 :Ce3+ and 55 to 65 parts by weight of matrix glass;
[0008] The matrix glass is composed of the following components:
[0009]
[0010] According to the fluorescent glass of the present invention, preferably, the fluorescent glass comprises 38 to 42 parts by weight of Y3Al5O 12 :Ce 3+ and 58 to 62 parts by weight of matrix glass;
[0011] The matrix glass is composed of the following components:
[0012]
[0013] According to the fluorescent glass of the present invention, preferably, the fluorescent glass comprises 40 parts by weight of Y3Al5O 12 :Ce 3+ and 60 parts by weight of matrix glass;
[0014] The matrix glass is composed of the following components:
[0015]
[0016]
[0017] According to the fluorescent glass of the present invention, preferably, the transmittance of the fluorescent glass to light in the wavelength range of 300-800 nm is greater than or equal to 40%.
[0018] According to the fluorescent glass of the present invention, preferably, the thermal conductivity of the fluorescent glass is greater than or equal to 0.2 W / m·K, and the luminous efficiency of the fluorescent glass is greater than or equal to 150 lm / W.
[0019] In another aspect, the present invention provides a method for preparing the fluorescent glass, comprising the following steps:
[0020] Y3Al5O 12 :Ce 3+ The fluorescent powder and the glass powder having the matrix glass composition are sintered at 670-820° C. for 15-55 minutes to obtain the fluorescent glass.
[0021] The preparation method according to the present invention preferably comprises the following steps:
[0022] Y3Al5O 12 :Ce 3+ The phosphor and glass powder were sieved through a 700-1300 mesh sieve; the sieved Y3Al5O 12 :Ce 3+The phosphor and the glass powder are ground for 2 to 5 hours in the presence of a monohydric alcohol containing 1 to 3 carbon atoms to obtain a ground raw material; the ground raw material is dried at 60 to 100° C. to obtain a dried ground raw material;
[0023] The dried and ground raw materials are sintered to obtain fluorescent glass.
[0024] The preparation method according to the present invention preferably further comprises the following steps:
[0025] The sintered product is cut into thin sheets with a thickness of 0.1 to 3 mm, and then polished to obtain fluorescent glass.
[0026] In another aspect, the present invention provides a vehicle headlight, wherein the vehicle headlight comprises the aforementioned fluorescent glass.
[0027] According to the automobile headlight of the present invention, preferably, the automobile headlight also contains a blue light chip.
[0028] The fluorescent glass of the present invention is composed of Y3Al5O 12 :Ce 3+ , SiO2, B2O3, Na2O, ZnO and CaO. Controlling these components within a specific content can improve the thermal conductivity and luminous efficiency of the fluorescent glass. Furthermore, the fluorescent glass of the present invention has high luminous intensity and transmittance. The sintering temperature and sintering time of the present invention can further improve the luminous intensity, transmittance, luminous intensity and transmittance of the fluorescent glass. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 1 and 2 are excitation spectra of the fluorescent glasses of Example 1 and Comparative Examples 1 to 5.
[0030] Figure 2 : are emission spectra of the fluorescent glasses of Example 1 and Comparative Examples 1 to 5. DETAILED DESCRIPTION
[0031] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0032] <Fluorescent glass>
[0033] The fluorescent glass of the present invention is composed of matrix glass and Y3Al5O 12 :Ce 3+ Composition. Y3Al5O 12 :Ce 3+It can be dispersed in the matrix glass. The matrix glass is composed of SiO2, B2O3, Na2O, ZnO and CaO. Of course, the fluorescent glass may contain some inevitable impurities. The fluorescent glass of the present invention does not contain components such as Al2O3, ZrO2, PbO, etc. The present invention finds that the above components are not conducive to improving the thermal conductivity and luminous efficiency of the fluorescent glass.
[0034] Y3Al5O 12 :Ce 3+ It is a yttrium aluminum garnet type yellow fluorescent material. 12 :Ce 3+ The content is 35 to 45 parts by weight; preferably 38 to 42 parts by weight; more preferably 40 parts by weight.
[0035] The matrix glass of the present invention is composed of SiO2, B2O3, Na2O, ZnO and CaO. The content of the matrix glass is 55 to 65 parts by weight, preferably 58 to 62 parts by weight, and more preferably 60 parts by weight.
[0036] SiO2 represents silicon dioxide. The content of SiO2 is 45 to 55 parts by mole, preferably 48 to 52 parts by mole, and more preferably 50 parts by mole.
[0037] B2O3 represents boron oxide. The content of B2O3 is 13 to 22 parts by mole, preferably 16 to 20 parts by mole, and more preferably 18 parts by mole.
[0038] Na2O represents sodium oxide. The content of Na2O is 20 to 30 parts by mole, preferably 24 to 28 parts by mole, and more preferably 26 parts by mole.
[0039] ZnO represents zinc oxide. The content of ZnO is 0.5 to 5 parts by mole, preferably 2 to 4 parts by mole, and more preferably 3 parts by mole.
[0040] CaO represents calcium oxide. The content of CaO is 0.5 to 5 parts by mole, preferably 2 to 4 parts by mole, and more preferably 3 parts by mole.
[0041] According to one embodiment of the present invention, the fluorescent glass comprises 40 parts by weight of Y3Al5O 12 :Ce 3+ and 60 parts by weight of matrix glass;
[0042] The matrix glass is composed of the following components:
[0043]
[0044] By controlling the content of each component within the above content range, the thermal conductivity, luminous efficiency, luminous intensity and transmittance of the fluorescent glass to light in the 300-800nm band can be improved.
[0045] The transmittance of the fluorescent glass of the present invention to light in the wavelength range of 300-800 nm is ≥40%; preferably, the transmittance is ≥50%; more preferably, the transmittance is ≥90%; most preferably, the transmittance is ≥97%.
[0046] The thermal conductivity of the fluorescent glass of the present invention is greater than or equal to 0.2 W / m·K; preferably, greater than or equal to 0.24 W / m·K; more preferably, greater than or equal to 0.26 W / m·K.
[0047] The luminous efficiency of the fluorescent glass of the present invention is greater than or equal to 150 lm / W; preferably, greater than or equal to 154 lm / W; more preferably, greater than or equal to 166 lm / W.
[0048] <Method for preparing fluorescent glass>
[0049] The preparation method of the fluorescent glass of the present invention comprises the following steps: 12 :Ce 3+ The fluorescent powder and the glass powder having the matrix glass composition are sintered to obtain the fluorescent glass.
[0050] The sintering temperature is 670-820°C. In some embodiments, the sintering temperature is preferably 740-770°C; more preferably 750-760°C. In other embodiments, the sintering temperature is 690-710°C. In still other embodiments, the sintering temperature is 790-810°C. This helps to improve the thermal conductivity, luminous efficiency and transmittance of the fluorescent glass.
[0051] The sintering time may be 15 to 55 minutes. In some embodiments, the sintering time is preferably 28 to 33 minutes; more preferably 30 to 32 minutes. In other embodiments, the sintering time is 18 to 22 minutes. In still other embodiments, the sintering time is 38 to 42 minutes. In still other embodiments, the sintering time is 48 to 52 minutes. This helps to improve the thermal conductivity, luminous efficiency and transmittance of the fluorescent glass.
[0052] The heating rate from the initial temperature to the sintering temperature may be 5 to 15°C / min, preferably 8 to 13°C / min, and more preferably 10 to 11°C / min.
[0053] The phosphor and the glass powder can be placed in a corundum crucible and then placed in a muffle furnace for sintering. After sintering, the crucible is cooled with the furnace to obtain a sintered product.
[0054] In some embodiments, the following steps are also included: 12 :Ce 3+ Phosphor powder and glass powder are sieved; the sieved Y3Al5O12 :Ce 3+ The phosphor powder and the glass powder are ground in the presence of a monohydric alcohol to obtain a ground raw material; the ground raw material is dried to obtain a dried ground raw material; the dried ground raw material is sintered to obtain a fluorescent glass. The sintering process is specifically as described above and will not be repeated here.
[0055] The mesh number of the sieve through which the fluorescent powder and the glass powder pass is 700-1300 meshes, preferably 800-1200 meshes, and more preferably 1000-1100 meshes.
[0056] The monohydric alcohol may be a monohydric alcohol containing 1 to 3 carbon atoms, for example, methanol, ethanol, n-propanol, isopropanol. Preferably, the monohydric alcohol is ethanol.
[0057] The grinding time can be 2 to 5 hours, preferably 3 to 4 hours. The grinding can be carried out in a corundum grinding jar.
[0058] The drying temperature may be 60 to 100°C, preferably 70 to 90°C, and more preferably 80 to 85°C.
[0059] The drying time may be 5 to 25 hours, preferably 10 to 20 hours, and more preferably 12 to 15 hours.
[0060] Drying can be carried out in an oven.
[0061] In some embodiments, the method further comprises the steps of cutting the sintered product into thin slices, and then polishing the thin slices to obtain fluorescent glass.
[0062] The thickness of the sheet may be 0.1 to 3 mm, preferably 0.3 to 2 mm, and more preferably 0.5 to 1 mm.
[0063] Diamond wire cutting machine can be used for cutting.
[0064] <Car headlights>
[0065] The automobile headlight of the present invention comprises the aforementioned fluorescent glass. Preferably, the automobile headlight also comprises a blue light chip.
[0066] The fluorescent glass of the present invention can emit yellow light under the stimulation of blue light, and thus produce white light after mixing with blue light. In addition, the fluorescent glass of the present invention has high thermal conductivity, luminous efficiency and luminous intensity, and visible light transmittance (300-800nm), and is a suitable material for fluorescent glass for automobile headlights.
[0067] Here is the test method:
[0068] Luminescence intensity: Use a fluorescence spectrometer model FLS1000 to test the luminescence intensity. Select blue light with a wavelength of 460nm as the excitation, and adjust the spectrometer and detector settings; place the sample at the measurement position, test the step of 0.5nm, scan from the wavelength range of 380nm to 780nm, and record the fluorescence intensity data at different wavelengths.
[0069] Transmittance: Use a UH4150 spectrophotometer to test the transmittance of the material. Specifically: first preheat the instrument and perform zero calibration, set the test wavelength to 300nm~800nm, then prepare the sample and place it in the light path for measurement. The instrument will record the transmittance data at different wavelengths.
[0070] Thermal conductivity: Use a TC3200 thermal conductivity meter to test. Preheat the system first, then clamp the sensor with two samples of the same specifications and fix them with weights. Set the test interval to 3 minutes and the acquisition time to 5 seconds in the software, perform "thermal conductivity measurement", repeat 3 times, take the average value, and get the thermal conductivity value of the fluorescent glass.
[0071] Luminous efficiency: The luminous efficiency of the fluorescent glass prepared under blue laser excitation was measured using a white light LED comprehensive test system (HAAS-2000) equipped with a 100 cm diameter integrating sphere and a 5 W blue laser.
[0072] Examples 1 to 6 and Comparative Examples 1 to 5
[0073] Y3Al5O 12 :Ce 3+ The phosphor and the glass powder with the components of 50SiO2-18B2O3-26Na2O-3ZnO-3CaO are sieved through a 1000 mesh sieve, and then the sieved phosphor and the glass powder are mixed to obtain a mixed raw material. The mixed raw material is placed in a corundum grinding jar; after adding ethanol to the corundum grinding jar, the mixed raw material is ground for 3 hours to obtain a ground raw material. The ground raw material is dried in an oven at 80° C. for 12 hours to obtain a dried ground raw material.
[0074] The dried and ground raw material is placed in a corundum crucible, and then sintered in a muffle furnace, and cooled with the furnace after sintering to obtain a sintered product. The heating rate from the initial temperature to the sintering temperature is 10°C / min.
[0075] The sintered product was cut by a diamond wire saw to form a thin sheet with a thickness of 0.5 mm; then it was polished to obtain fluorescent glass.
[0076] The mass ratio of phosphor and glass powder, sintering temperature and sintering time are shown in Table 1. The luminous intensity, transmittance, thermal conductivity and luminous efficiency are shown in Table 1.
[0077] Figure 1 1 and 2 are excitation spectra of the fluorescent glasses of Example 1 and Comparative Examples 1 to 5. Figure 2 is the emission spectrum of the fluorescent glass of Example 1 and Comparative Examples 1 to 5. Figure 1 and Figure 2 It can be seen that the fluorescent glass of the present invention has a strong emission peak in the 545nm band under the excitation of 460nm blue light.
[0078] Table 1
[0079]
[0080] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be thought of by those skilled in the art shall fall within the scope of the present invention.
Claims
1. A fluorescent glass, characterized in that: The fluorescent glass comprises 35 to 45 parts by weight of Y3Al5O 12 :Ce 3+ and 55 to 65 parts by weight of matrix glass; The matrix glass is composed of the following components: composition:
2. The fluorescent glass according to claim 1, characterized in that: The fluorescent glass comprises 38 to 42 parts by weight of Y3Al5O 12 :Ce 3+ and 58 to 62 parts by weight of matrix glass; The matrix glass is composed of the following components: composition:
3. The fluorescent glass according to claim 1, characterized in that: The fluorescent glass is composed of 40 parts by weight of Y3Al5O 12 :Ce 3 + and 60 parts by weight of matrix glass; The matrix glass is composed of the following components: composition:
4. The fluorescent glass according to any one of claims 1 to 3, characterized in that: The transmittance of the fluorescent glass to light in the wavelength range of 300 to 800 nm is greater than or equal to 40%.
5. The fluorescent glass according to any one of claims 1 to 3, characterized in that: The thermal conductivity of the fluorescent glass is greater than or equal to 0.2 W / m·K, and the luminous efficiency of the fluorescent glass is greater than or equal to 150 lm / W.
6. The method for preparing fluorescent glass according to any one of claims 1 to 5, characterized in that: The steps include: Y3Al5O 12 :Ce 3+ The fluorescent powder and the glass powder having the matrix glass composition are sintered at 670-820° C. for 15-55 minutes to obtain the fluorescent glass.
7. The preparation method according to claim 6, characterized in that: The steps include: Y3Al5O 12 :Ce 3+ The phosphor and glass powder were sieved through a 700-1300 mesh sieve; the sieved Y3Al5O 12 :Ce 3+ The phosphor and the glass powder are ground for 2 to 5 hours in the presence of a monohydric alcohol containing 1 to 3 carbon atoms to obtain a ground raw material; the ground raw material is dried at 60 to 100° C. to obtain a dried ground raw material; The dried and ground raw materials are sintered to obtain fluorescent glass.
8. The preparation method according to claim 6, characterized in that: The following steps are also included: The sintered product is cut into thin sheets with a thickness of 0.1 to 3 mm, and then polished to obtain fluorescent glass.
9. A car headlight, characterized in that: The automobile headlight comprises the fluorescent glass according to any one of claims 1 to 5.
10. The automobile headlight according to claim 9, characterized in that: The automobile headlight also contains a blue light chip.
Citation Information
Patent Citations
Low-melting-point fluorescent glass for white light LED and preparation method thereof
CN101643315A
Phosphor-dispersed glass
CN105121375A